DAKWAH DALAM MASYARAKAT MULTIKULTURAL - Nawawi, Nawawi (Fakultas Dakwah IAIN Purwokerto, 2012)
Indonesia is a country which has so many ethnicities, tribes, cultures, languages, andreligions. Such diversity is prone to conflict and discord and therefore, there must be asystematic, programmed, integrated, and sustainable effort to maintain the integrity of thenation and as a multicultural country.A step to be taken to realize it is by planting a multicultural understanding to thesociety. Planting a multicultural understanding is not intended to eliminate differences but toeliminate bias, develop dialogs and get to know the differences among them, so that mutualrespect and appreciation can be achieved. One form of planting a multicultural understandingcan be a dakwah activity which applies a cultural approach that is grounded in universalvalues of humanity.